4 - The Quagmire of US Militarism in Africa - Campbell, Horace G. (Africa Development, 2020)
In the period of the so-called War on Terror, US militarism in Africa has intensified to include the weaponisation of finance, the weaponisation of trade, psychological warfare, information warfare and the deployment of private military contractors in the so-called ‘security sector reform’. In the face of African resistance, the deployment of the US Africa Command (AFRICOM) has unleashed disaster after disaster, from the catastrophic failures in Libya to the sequences of failure in the Sahel region. The death of four US service personnel in Niger in 2017 along with the killing of non-white soldiers in Africa by white supremacists in the US military have similarly exposed the deficiencies and racism inherent in the US security establishment. In the context of US military involvement in the Middle East, currency wars and capital flight from Africa, the US travel ban on Muslims exposed the contradictions of African allies and sharpened their clear alliance with the empire despite the overt racism of Making America Great Again. The quagmire of US militarism is now exposing the current manifestations of white supremacy. In addition to contextualising and accounting for these developments across the continent, this article argues that progressive scholars cannot be bystanders in the struggles against militarised global apartheid. Africans must grasp the lessons of global racism to re-ignite the progressive pan-African traditions that were able to roll back apartheid in its crude form.